THE ROLES OF ETHICS IN WAQF MANAGEMENT: CASE OF JAWHAR - Kamri, Nor ’Azzah (Jurnal Syariah, 2010)
Waqf (endowment) is one of the practices that are prescribed in Islam. It provides extensive benefit to the waqf founder (waqif) as well as to the receiver (mawquf). Therefore, property governed under waqf should be managed ethically to ensure the benefit can be derived by all. This article discusses the importance of applying a code of ethics in waqf institutions. This article also presents the JAWHAR code of ethics as an empirical instance to be implemented by waqf institutions in administering waqf matters. It is believed that the implementation of this code of ethics can create a professional culture in waqf management and return the waqf institution to the glory that was attained in the past.